Tapestry : Listening & Speaking 1 - Cheryl Benz, Kara Dworak (Heinle & Heinle Publishers, 2000)
Designed for use in Arab and Islamic cultures, Tapestry Middle east edition is the ideal choice for culturally appropriate English language instruction